Paradigma Baru Pembelajaran PKn di Sekolah Dasar dalam Membentuk Karakter Siswa di Era Revolusi Industri 4.0: New Paradigm of Civics Learning in Elementary Schools in Forming Student Character in the Era of Industrial Revolution 4.0 - Riska Armianti; Bungana, Reh; Setiawan, Deny (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The new paradigm in Civic Education (PKn) learning in elementary schools is very important in shaping students' character in the digital era. This study aims to evaluate how innovative approaches and methods in PKn learning can create students who have integrity, ethics, and adequate digital skills. Through literature studies and empirical data analysis from several elementary schools in Indonesia, it was found that technology integration in PKn learning can increase student interest and engagement. Project-based learning, the use of interactive digital media, and internet-based educational applications are important tools in this process. Approaches that emphasize collaboration, critical discussion, and self-reflection have also proven effective in instilling citizenship values ??and digital ethics. The results of this study indicate that by adopting a new paradigm that is adaptive to technological developments, PKn learning in elementary schools is not only able to shape good student character, but also prepare them to become smart and responsible citizens in the digital era. These findings provide important implications for curriculum development and educational practices in elementary schools, especially in facing the challenges and opportunities presented by the digital era.